2016
DOI: 10.1093/ecco-jcc/jjw022
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Anti-Tumour Necrosis Factor-treated Inflammatory Bowel Disease Patients After the Implementation of Preventive Measures: Compliance With Recommendations and Safety of Retreatment

Abstract: Tuberculosis could still occur in anti-TNF-treated IBD patients despite compliance with recommended preventive measures. A significant number of cases developed when these recommendations were not followed. Restarting anti-TNF treatment in these patients seems to be safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 75 publications
2
39
0
2
Order By: Relevance
“… 1 For these reasons, screening and treatment for LTBI before initiating anti-TNF therapy are strongly recommended by many scientific organizations and health authorities worldwide. 6 7 8 9 10 11 12 13 14 15 16 17 18 19…”
Section: Management Of Latent Tb In Preparation For Anti-tnf Therapymentioning
confidence: 99%
See 2 more Smart Citations
“… 1 For these reasons, screening and treatment for LTBI before initiating anti-TNF therapy are strongly recommended by many scientific organizations and health authorities worldwide. 6 7 8 9 10 11 12 13 14 15 16 17 18 19…”
Section: Management Of Latent Tb In Preparation For Anti-tnf Therapymentioning
confidence: 99%
“…In a multicenter, retrospective study from Spain, 60% (30/50) of TB cases in anti-TNF-treated patients with IBD developed TB despite properly following the national guidelines for LTBI treatment, including 5 patients who received LTBI chemoprophylaxis. 13 In a retrospective observational study from Greece, of 36 patients who completed LTBI treatment prior to anti-TNF therapy, 7 developed active TB at 2 to 35 months after anti-TNF therapy initiation. 40 In a retrospective observational study from South Korea, the active TB incidence was 1,107 per 100,000 patient-years in LTBI-positive anti-TNF users who received standard LTBI treatment and 490 per 100,000 patient-years in LTBI-negative anti-TNF users.…”
Section: Monitoring During Anti-tnf Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the risk of incident TB has been reduced substantially . Nonetheless, this strategy fails to completely eliminate the risk of TB after anti‐TNF‐α therapy . Moreover, one study indicated that active TB was more common in patients with IBDs even before anti‐TNF‐α treatment was started …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Nonetheless, this strategy fails to completely eliminate the risk of TB after anti-TNF-a therapy. 8 Moreover, one study indicated that active TB was more common in patients with IBDs even before anti-TNF-a treatment was started. 9 Only a few studies have evaluated the risk of incident active TB in patients with IBDs.…”
Section: Introductionmentioning
confidence: 99%